Direito autoral na representação capitalista: o caso da indústria fonográfica no Brasil - Cerqueira, Amanda Patrycia Coutinho de (2013)
Based on the analysis of capitalist restructuring, this thesis aims at examining the movement of contemporary capitalism which explains the convenience and valorization of cultural production, as well as the authorial rights role within this context. The very Economy increasingly depends on both property and services provided by this medium. Culture is strongly connected with technology. On being so, culture is no longer residual inducing to capital accumulation. On the contrary, culture is an activity subscribed to production and reproduction of capital. This movement is currently legitimate through the neo-development discourse, which relates culture to development and maximization of the protective standards of IP (Intellectual Property), and therefore these factors lead to concepts, such as cultural Economy, and creative Economy. Accordingly to all factors herein referred to, this study raises a hypothesis, which is proposing that authorial rights, before paying author s remuneration, assure both controlled scarcity and the extraction of profits for capital accumulation. It thus becomes clear that music industry comes out as an analytical instrument. Upon associating Political Economy and Cultural Studies, one intends to accomplish a thorough comprehension of authorial rights, including their contradictions and updated meaning. Moreover, this study is meant to contribute to further researches on this increasing and contemporary field, which is concerned with resolutions and public policies. The latter are capable of furnishing measures to decentralize the cultural production, besides pointing out the structural contradictions of society.